The Effect of Good Corporate Governance (GCG) on Financial Performance with Company Size as a Moderating Variable - Wiwit Indah Lestari Ningsih; Erma Setiawati; Rina Trisnawati (Journal Research of Social Science, Economics, and Management, 2023)
Purpose: This research aims to analyze the effect of insider share ownership, board size, independent board of commissioners, audit committee on financial performance with Company Size as a moderating variable. Insider share ownership, board size, independent board of commissioners and audit committee are proxies for Good Corporate Governance (GCG). Methodology: The Indonesia Stock Exchange (IDX) website provides access to secondary data used in this study. Information about businesses listed on the IDX is included in this data. Purposive sampling was used to choose the sample, which implies the researcher purposefully chose businesses that matched the study's criteria. Eviews 9 software was used for data analysis. Results: The study's conclusions provide the following details: The size of the board of commissioners (Board Size), the number of directors on the board of directors (Board Size), and the existence of an independent board of commissioners (Independent Board of Commissioners) have little impact on the company's financial success. The size of the board of directors (Board Size) has a significant impact on the financial performance of the company. This may be proof that management and decision-making within the corporation are impacted by the size of the board of directors. The size of the organization modifies the relationship between the audit committee and financial performance. As a result, the size of the audit committee determines how much it influences financial performance.